Kemiskinan Pemikiran dalam Kajian Islam di Indonesia Menuju Ilmu-ilmu Sosial Profetik - Dawam Rahardjo (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2015)
In relation to the criticism that the study of Islamic thought is still dominated by bayani approach, al-jabri and Hassan Hanaf advocated for more rational approach or approaches developed Burhani. Bayani epistemology dominance has became the target of criticism liberal Islamic thinkers. The main hypotheses that I would suggest is that science Islam (Islamic science) it is essentially a science of piece (peace science) through the analysis of the relationship between human beeings with each other and with nature. The second hypothesis is that Islamic science as a science of peace it needs to begin with review of Islamic science traditional and perfoms studies on social monotheism, social jurisprudence and social Sufim. The third hypothesis is that methodologically, the Islamic science as a science of peace held in the social and humanitarian (humanities) through the study of social sciences prophetic.